Integrasi Kearifan Lokal Petis Rujak Cingur pada Pembelajaran Sistem Koloid untuk Meningkatkan Keterampilan Berpikir Kreatif - Titik Wulandari; Beni Setiawan; Utama Alan Deta (PendIPA Journal of Science Education, 2026)
This research is motivated by the low level of students' creative thinking skills in chemistry lessons, which tend to be teacher-centered and emphasize theoretical mastery of concepts. Furthermore, colloidal systems are considered difficult to understand due to their abstract nature and lack of relevance to everyday life. Therefore, contextual learning is needed through the integration of ethnoscience and local culture. This study aims to develop a valid, practical, and effective ethnoscience-based chemistry learning tool for colloidal systems, specifically petis rujak cingur, to enhance students' creative thinking skills. This research is a developmental study using the ADDIE model. A trial was conducted at Hang Tuah 1 High School, Surabaya, in the odd semester of the 2025–2026 academic year using a One-Group Pretest-Posttest Design. The learning tool was validated by two Science Education lecturers and two Science teachers. Data collection techniques included observation and tests. The results showed that the developed learning tool was declared valid based on the validator's review. The practicality of the device is demonstrated through the implementation of learning with a percentage of 76% and 80% in the implemented category. The effectiveness of the device is seen from the increase in the pre-test and post-test results of students' creative thinking skills with an average pre-test score of 57.7429 and a post-test score of 82.5714. The results of the paired sample t-test obtained a significance value of 0.000 (<0.05) which indicates a significant difference between the pre-test and post-test results. In addition, the N-Gain value of 0.5878 is in the moderate category. Based on the results of the study, it can be concluded that the ethnoscience-based chemistry learning device of rujak cingur petis on the colloidal system material is valid, practical, and effective in improving students' creative thinking skills.